Social Media Analysis Of The Brand Image Of Bakso Gajah Bang Ucok Products At Tuasan Tempuling Medan - Micha Siar Meiriza; Fikri Alfahmi Siregar; Okta Viani Kristin; Nabila Boru Lubis; Anggita Kinanti (ATRABIS Jurnal Administrasi Bisnis (e-Journal), 2024)
This study examines the effect of social media use on the brand image of UMKM products with a case study of Bakso Goreng Gajah Bang Ucok in Medan. In the growing digital era, social media has significantly changed the marketing landscape for UMKM businesses. This research method uses a descriptive qualitative approach through observation data collection, direct interviews with business owners, and documentation of the business. The results showed that social media, especially TikTok as the main marketing media, has a significant positive impact on business development. The use of content strategies that trigger emotional responses, personalized approaches and soft selling, as well as active interaction with customers has proven effective in increasing sales. The effective implementation of the strategy had a positive impact, not only on increasing sales figures in the company's operational areas, but also attracted the attention of mainstream media and influential content creators. Despite facing several obstacles such as poor content assessment and feedback, this study proves that proper and sustainable social media management is the key to achieving business success and growth for UMKMs in today's digital age.